ON THE ISSUE OF AUTHOR'S AND NEIGHBOURING RIGHTS ENCROACHMENT - V. Kondrashina (Russian Journal of Economics and Law, 2008)
The article views the issue of corpus delicti stipulated by Parts 1-3 of Article 146 of the Russian Criminal Code, the importance of the correct understanding of this case, and gives the comparative study of this issue in the foreign criminal codes.